2017
DOI: 10.1111/iju.13386
|View full text |Cite
|
Sign up to set email alerts
|

Bone scan index: A new biomarker of bone metastasis in patients with prostate cancer

Abstract: Bone scintigraphy is one of the first-line imaging modalities for the screening and follow up of bone metastasis in patients with prostate cancer. The amount (%) of bone metastasis can be calculated using a bone scan index thanks to recent advances in quantitative bone scintigraphy. Since an artificial neural network was applied for hot-spot characterization and quantitation, the bone scan index has become a simple, reproducible and practical means of quantifying bone metastasis. The bone scan index is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
0
44
0
1
Order By: Relevance
“…11 C‐choline or 18 F‐choline PET/CT has mostly been investigated in restaging after primary treatment . However, its diagnostic accuracy is still suboptimal .…”
Section: Evidence Acquisitionmentioning
confidence: 76%
See 1 more Smart Citation
“…11 C‐choline or 18 F‐choline PET/CT has mostly been investigated in restaging after primary treatment . However, its diagnostic accuracy is still suboptimal .…”
Section: Evidence Acquisitionmentioning
confidence: 76%
“…84 11 C-choline or 18 F-choline PET/CT has mostly been investigated in restaging after primary treatment. 85 However, its diagnostic accuracy is still suboptimal. 86 Reported data show a variable DR according to PSA level, ranging from 36% if PSA relapse is <1 ng/mL to 73% if PSA at relapse is >3 ng/mL.…”
Section: Re-staging After Primary Treatmentmentioning
confidence: 99%
“…The recommendations of the St. Gallen Advanced Prostate Cancer Consensus Conference 2015 emphasize the importance of regular treatment monitoring and risk-adapted approaches. 10 A Japanese registry of patients with prostate cancer and bone metastasis has been established and their baseline characteristics were determined. Therefore, the BSI could be a promising quantitative marker of radiographic progression.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the extent of disease can be determined to some degree by counting hot spots, the complex nature of radiotracer accumulation hampers the general applicability of bone scans. 10 Several prior studies have shown that computer-assisted analysis improves classification and is thus applicable to diagnostics. [5][6][7] This software is called BONENAVI (FUJIFILM RI Pharma, Tokyo, Japan) in Japan, and was revised from the original EXINI bone software (EXINI Diagnostics, Lund, Sweden) in a multicenter project involving a large Japanese database.…”
mentioning
confidence: 99%
“…2 Eight years after that work was published, Sadik et al were the first to report use of a computer-assisted diagnosis system for calculating BSI. 4,5 As noted above, BSI has recently become recognized for its ability to provide useful information for PC patients with bone metastatic disease. 4,5 As noted above, BSI has recently become recognized for its ability to provide useful information for PC patients with bone metastatic disease.…”
mentioning
confidence: 99%